The Estimation of Students’ Scientific Work Assessment at Pekan Olahraga Riset Dan Ornamen Seni (Poros) Ii of Eastern Indonesia Islamic Universities 2021 - Lian Gafar Otaya; Herson Anwar; Mujahid Damopolii (At-Tarbiyat, 2021)
The assessment of scientific works at Pekan Olahraga, Riset dan Ornamen (POROS) II Competition of Eastern Indonesia Islamic Universities 2021 in the field of Islamic education, Islamic Law, Ushuluddin, and Islamic economy involves three judges who assess some components such as the format of works, creativity, topic, data, sources, analysis, synthesis, and conclusion which possibly bring differences among the judges. In addition, the weight of each component is also different. The criteria in the scoring can affect the consistency of the judges. Therefore, it is essential to determine the judges' reliability coefficient of the assessment. This study is quantitative research because its primary data are the scores of the judges’ reviews. The reliability estimation of this study used the variants analysis approach and procedure based on the generalizability theory through the concept of G-Study with multifacet design. Based on the analysis, it was obtained that the reliability coefficient of the combined score of participants’ assessment, especially in the field of Islamic education, was 0.90920, which means that the assessment instrument used in the scientific works of POROS II Competition 2021 in Islamic education was reliable in determining the best results.